PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN MIE LEMONILO PADA MASYARAKAT KOTA PALEMBANG - Madeleine, Madeleine; Oktavia, Diana (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract : This research aims to prove the influence of product quality and price perception on purchasing decisions for Lemonilo noodles among the people of Palembang City. The variables used in this research are product quality, price perception and purchasing decisions. The type of data used in this research is primary data. The population in this study were all consumers who had purchased Lemonilo Noodles from the Palembang City Community and the sample in this study was 100 respondents who had met the criteria using a purposive sampling technique. The research method used in this research is quantitative. The data analysis technique used is multiple linear regression analysis. The results of the research show that product quality and price perception have a positive and significant effect on purchasing decisions.Kata kunci: Product Quality, Price Perception and Purchasing Decisions